2020
DOI: 10.3390/nu12061805
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gastrodin against Lead-Induced Brain Injury in Mice Associated with the Wnt/Nrf2 Pathway

Abstract: Gastrodin (GAS), the main phenolic glycoside extracted from Gastrodia elata Blume, exhibited potential neuroprotective properties. Here we examined the protective effects of GAS against lead(Pb)-induced nerve injury in mice, and explores its underlying mechanisms. Our research findings revealed that GAS improved behavioral deficits in Pb-exposed mice. GAS reduced the accumulation of p-tau and amyloid-beta (Aβ). GAS inhibited Pb-induced inflammation in the brain, as indicated by the decreased levels of pro-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 43 publications
4
7
0
Order By: Relevance
“…Substantially, WERG-H significantly alleviated D-gal/AlCl 3 -stimulated cognitive impairment, p-Tau Thr231 protein formation, and pathological changes. Consistent with the present study, gastrodin significantly inhibited lead-induced p-Tau accumulation in the mouse brain (Liu et al, 2020). Similarly, another study confirmed that gastrodin suppressed the deposition of p-Tau in the brain of the unilateral intracerebroventricular injection of the Aβ 1-42 mouse model (Luo et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Substantially, WERG-H significantly alleviated D-gal/AlCl 3 -stimulated cognitive impairment, p-Tau Thr231 protein formation, and pathological changes. Consistent with the present study, gastrodin significantly inhibited lead-induced p-Tau accumulation in the mouse brain (Liu et al, 2020). Similarly, another study confirmed that gastrodin suppressed the deposition of p-Tau in the brain of the unilateral intracerebroventricular injection of the Aβ 1-42 mouse model (Luo et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…However, this is not always the case. The experiments of Liu et al [ 67 ] and Liu et al [ 68 ] showed that lead inhibited the expression of Nrf2 signaling-related proteins and then induced oxidative stress, inflammation, and apoptosis. Interestingly, our experimental results are not entirely consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Through this way, GAS can significantly reduce nerve edema after ischemia and improve neuronal apoptosis [ 68 70 ]. Gastrodin can also activate Wnt/ β -catenin signaling pathway through NRF2-mediated antioxidant signals and reduce cycx-2 (COX-2) activation, showing neuroprotective properties [ 71 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Common toxic substances, such as A β , glutamate, and NO, increase, and neurotrophic substances decrease in VaD patients [ 74 ]. Gastrodin can reverse the above pathological changes and play a role in increasing neuronal survival, improving synaptic function and promoting neural differentiation [ 71 ]. Studies have shown that GAS can reduce the expression of A β 1-40/42, APP, and β -site APP Exceller enzyme 1.…”
Section: Resultsmentioning
confidence: 99%